Nutrition of elite football players: Periodisation approach and match day nutritional guidelines - Rajic, B.; Karisik, S. (Serbian Journal of Sports Sciences, 2021)
Football is a globaly popular game which constantly evolving and seeking for new requirements in physical, tactical and techical demands. Nutrition plays an important role in seeking high performance during season, with special focus on the match day nutritional strategy. The science task is to provide guidelines in ellite players crucial aspects such as match day nutrition, periodisation of nutrition, body composition, travel environment of football players, cultural diversity and religious requirements, rehabillitation and return to play. Our intention is to provide a set of practical recommendations with special emphasyze in the fotball match day nutrition plan.